Anticancer Potential of Tabernaemontana divaricata Extracts against HeLa and Vero Cell Lines (Asian Journal of Pharmaceutics (AJP), 2026)
Background: The history of India has recorded about its ancient medical practices, which date back to centuries when the use of green plants of various kinds was used to treat most of the diseases in such critical periods. Such one is the perennial evergreen shrub Tabernaemontana divaricata, which has been used as traditional medicine. It is mainly famous with its phenols and flavonoids. These compounds are associated with different pharmacological activities.Objective: Therefore, the leaves of T. divaricata were collected, extracted, and studied in this research to establish their anticancer effects. Nevertheless, its anticancer properties have received less research; hence, the objective of the research was to examine the in vitro anticancer effects of T. divaricata leaf extract isolated with the aid of a crude solvent extraction. Materials and Methods: Past research has demonstrated that it has possible anti-inflammatory, anti-microbial, and antioxidant properties. The anticancer activity was confirmed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay used to evaluate the inhibition of cell growth in the in vitro anticancer research that was done on Vero and HeLa cell lines. Results: The findings revealed the anti-cancer activity of T. divaricata on the HeLa cell lines. In addition, docking showed that 2,2-dibromocholestanone has high binding affinity to Caspase 3, p53, and nuclear factor kappa -B and indicates potential use in anticancer. Conclusion: These results indicate the potential anticancer properties of T. divaricata leaf extract and support its possible use in anticancer research.